Cabinet Decontamination Using Formaldehyde. (June 2017) - Ngabo, Didier; Pottage, Thomas; Bennett, Allan; Parks, Simon
Formaldehyde fumigation is the most widely used method for terminal decontamination of biosafety cabinets in the UK. International standards define volumes of Formalin and water to be used for an effective fumigation. However, no published information is available showing that these levels are appropriate or effective. Studies have been undertaken to optimize the volumes of fumigant required to achieve 6 log reductions of bacterial spores within 2 sizes of biosafety cabinet. The tests have shown effective cycles can be achieved using significantly lower levels of fumigant than are recommended within the European Standard for biosafety cabinets and UK guidance. There is clear evidence of stratification of the fumigant within the cabinets with the time taken to achieve a 6 log reduction depending on the position within the cabinet and the local relative humidity.